William A. Smalley, Chia Koua Vang y Gnia Yee Yang. (Trad. Mitt Moua) Mother of Writing; the Origin and Development of a Hmong Messianic Script. Chicago y Londres: The University of Chicago Press, 1990. xiii, 221 pp. - Thomas Cedric Smith Stark (El Colegio de México, A.C., 1996)
-